2008
DOI: 10.1590/s1517-83822008000300015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic differentiation of avian Escherichia coli by RAPD-PCR

Abstract: Escherichia coli is one of the most important bacterial avian pathogens and a common inhabitant of the gastrointestinal tract of animals. Most pathogenic E. coli can not be differentiated biochemically or by classic microbiologic methods. Molecular typing methods, particularly PCR, facilitated epidemiological and ecological studies of bacteria. Here we describe the application of a random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR) for molecular genetic differentiation of E. coli isolates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
1
11
0
2
Order By: Relevance
“…17 Additionally, Salehi et al concluded that the RAPD can be a useful method for determining the genetic differences between the E. coli isolates. 18 Similar to other studies, the analysis of dendrogram represented high genetic diversity in E.coli isolates, indicating the participation of different pollution centers in spreading the bacteria. 19,20 Similarly, the results of the current study demonstrated that different isolates of the same E. coli species yielded no similar phylogenetic relationship.…”
Section: Discussionsupporting
confidence: 84%
“…17 Additionally, Salehi et al concluded that the RAPD can be a useful method for determining the genetic differences between the E. coli isolates. 18 Similar to other studies, the analysis of dendrogram represented high genetic diversity in E.coli isolates, indicating the participation of different pollution centers in spreading the bacteria. 19,20 Similarly, the results of the current study demonstrated that different isolates of the same E. coli species yielded no similar phylogenetic relationship.…”
Section: Discussionsupporting
confidence: 84%
“…The combined regimen of such natural products with antibiotics for better effectiveness have long been advocated [19]. Rich phytochemical constituents observed in this study are secondary metabolites already reported with protective roles [20].…”
Section: Discussionmentioning
confidence: 54%
“…And the use of various primers for P. aeruginosa generated a total of 131 amplified fragments of between 200 to 300 bp, this more than the number of fragments generated from Staphylococcus aureus and Escherichia coli while using the same number of primers (Onasanya et al, 2003;Salehi et al, 2008;Shehata, 2008).…”
Section: Results and Dicussionmentioning
confidence: 99%